Inadvertent Migration of Hepatic Artery Pseudoaneurysm Coil during Endoscopic Retrograde Cholangiopancreatography - Riad Alchanan; Rajdeep Chhina; Ghali Salahia; Dean Huang; Dylan lewis (The Arab Journal of Interventional Radiology)
We report a case of a 72-year-old male with a cascade of complications being diagnosed as an acute cholecystitis. The cascade includes iatrogenic pulling of coils, which were placed for treatment of right hepatic artery pseudoaneurysm, into the common bile duct (CBD) in an attempt for removal of the misplaced/migrated CBD plastic stent inserted by endoscopic retrograde cholangiopancreatography (ERCP). The case demonstrates a series of mishaps leading to a rare complication of iatrogenic migration of transarterial coil in the gastrointestinal tract. This could be the first case of coil migration as a complication of ERCP due to suboptimal stenting/removal techniques.